Strategi pembelajaran efektif berbasis mobile learning pada sekolah dasar - Nasution, Muhammad Irwan padli (IQRA: Jurnal Perpustakaan dan Informasi, 2016)
We now accept the fact that learning is a lifelong process of keeping abreast of change. And the most pressing task is to teach people how to learn (Peter Drucker).Â  An educator using various technologies in the process of teaching and learning activities that are useful to enhance the effectiveness of teaching and learning in the classroom. Has developed a wide variety of learning strategies from simple to more complex models even complicated and require a lot of tools in its application. In the present era the use of ICT (Information and Communication Technology) in the learning process has become a common and ordinary. ICT use can be made of multimedia teaching materials with the concept of learning by playing fun and developed on an application-based learning mobile learning. The use of mobile devices (mobile device) is very useful to support the learning process and increase flexibility in teaching and learning activities.